Intersections: A Journey - Baglow, John (Anthropologica, 2013)
This exercise in authoethnography is divided into two parts: first, an impressionistic account of a journey to New Zealand/Aotearoa by the author and his family to scatter the ashes of his partner at Cape Reinga (Te Rerenga Wairua) in a Maori ceremony, and second an analysis of the first part, problematizing the notions of "culture" and "hybridity" and abandoning both in favour of a dialogical approach to differ ence and the "Other."